Evaluation of seakeeping model tests in open waters using two submarine hull forms - Büsken, Wiebke; Krüger, Stefan (American Society of Mechanical Engineers, 2023)
In this paper, the experimental procedure of seakeeping model tests in open waters with two free-running, remotely-controlled submarine hull forms as realized on Eckernförde Bay from October 2021 to April 2022 is presented. The objective of performing such model tests with surfaced submarines at various conditions of stability, speeds and encounter angles in natural seaway is explained. A summary of the qualitative observations concerning the different identified phenomena, which lead to large motion amplitudes, is given in this paper along with a quantitative evaluation of the model tests by statistical analysis of selected test runs. As part of the results, different heeling moments, which were observed to attack the surfaced submarine during these model tests, are discussed, especially in regard to their inclusion in the recently developed new stability standard for the intact surface stability of submarines of the German Navy.